Hells Bells: unique speleothems from the Yucatán Peninsula, Mexico, generated under highly specific subaquatic conditions - Stinnesbeck, Wolfgang; Frey, Eberhard; Zell, Patrick; Hering, Fabio; Frank, Norbert; Arps, Jennifer; Isenbeck-Schröter, Margot; Ritter, Simon M. (Palaeogeography, palaeoclimatology, palaeoecology, 2018)
We here report on a type of meter-sized pendant speleothem growing under water in the submerged El Zapote sinkhole (cenote) west of Puerto Morelos on the Mexican Yucatán Peninsula. These conical, mantle-shaped downward expanding and diverging calcareous structures, here termed as Hells Bells, are yet unreported in the scientific literature. They are characterized by bell- or trumpet shaped longitudinal and circular, elliptical or horse-shoe-like horizontal cross-sections. Hells Bells grow downward, based on the downward divergence of the structures and the horizontally laminated internal texture of both blade-shaped spar calcite and microspar laminae. Age dating confirms that Hells Bells are young (<4500yr) and formed in a subaquatic environment. They grow under lightless conditions in a stratified water body, which is characterized by a fresh water body overlying a salt water body with a stagnant transition zone (halocline) of several meters. We hypothesize that the growth of these structures is mediated by specific physical and biogeochemical conditions above and in the halocline. Stagnant hydraulic conditions led to extensive diffusion profiles of several nutrients including calcium originating from the salt water body. Dissolved organic carbon from the fresh water is microbially oxidized in the upper part of the halocline, where a distinct redox zonation was identified from oxic to anoxic conditions. Degradation processes combined with slightly alkaline pH values as well as the diffusive transport of calcium into this zone may induce an increase in calcite oversaturation. Phylogenetic analysis of the community on the surface of the Hells Bells suggests the presence of microorganisms involved in the nitrogen-cycle, from which some potentially have the capability to increase the pH by autotrophic growth and denitrifying activity, thus supporting calcite precipitation. The growth of Hells Bells is strictly dependent on the elevation of the halocline. This offers a wide potential for the use of Hells Bells as archives of paleo-hydrological conditions during the Holocene, e.g. the variation of thickness of the fresh water lens on the Yucatán Peninsula.